Safety in chemical production - Whiston, J. ([S.l.] : Wiley-Blackwell, 1992)
The first IUPAC Workshop on Safety in Chemical Production was established in recognition of the fact that, at present, University teaching in this area is inadequate and significant difficulties and dangers arise when chemists transfer from the academic to the industrial environment. Furthermore it had become evident from such tragedies as that which occured at Bhopal that there was a lack of standard procedure for transferring safety technology from the developed to the developing world. Finally, whilst there were a number of groups active in the fields of safety education, there was no unified and international approach to this important aspect of the technology. The primary objectives of the Workshop were: 1. To provide a unified basis at University level for safety education in chemical technology. 2. To provide, with Case Studies (especially in the field of Hazard Analysis and Risk Reduction) a series of model lectures for use in Universities. 3. A programme for future development. IUPAC were uniquely placed to establish the first workshop.
Keywords: chemical production